Analisis Tingkat Kebisingan dan Upaya Pengendalian Kebisingan di PT. XYZ - Ghora, Akbar Ghora Putra; Satoto, Handy Febri (SURYA TEKNIKA, 2025)
Noise is a major issue in industrial environments, including at PT. XYZ, which manufactures sack and woven bags. The production process involves machines that generate high noise levels, potentially causing hearing loss among workers. This study aims to analyze and map noise levels in the work area and recommend appropriate control measures. Data were collected using the grid lines method at 18 points with a Sound Level Meter and mapped using Golden Surfer software. Results show that several locations exceeded the 85 dB threshold set by the Ministry of Manpower, with the highest level of 99.1 dB found in the Circular Loom area. Risk analysis was conducted to evaluate health impacts, and noise control strategies were developed based on the hierarchy of controls, including elimination, substitution, engineering controls, administrative measures, and the use of personal protective equipment.